Sex-based age differences in the Norwegian top soccer leagues - Berg, I.; Dalen, T.; Solli, G. S. (Journal of Human Sport & Exercise, 2023)
This study aims to examine sex-based age differences in the Norwegian top soccer league, the relationship between age and performance level, and the presence of the relative age effect (RAE) in the same population of players. Players` birthdates were obtained from publicly available databases, and the total sample comprised 663 players (231 women, 432 men) from 26 teams (10 women`s teams and 16 men`s teams). For the RAE analyses, birth months were categorised in birth quartiles: Q1: January-March, Q2: April-June, Q3: July-September, Q4: October-December. The median age of the players was significantly lower for women than for men [22.1 (15.0-38.2) vs. 24.5 (15.5-38.4) p < .001]. A very large correlation between the median age of the team and the team performance was found in the women`s league (rs(10) = -0.72, p = .019), while no correlation was found in the men`s league (rs(16) = 0.22, p = .405). Chi-square analysis showed a difference between the observed and expected birth quartile distributions for the total sample, male players, and female players (p < .05). The lower age observed for the women than for the men indicates the need to prolong female players` careers through greater support, allowing them to reach their performance potential.